Optimization of an elisa using a 50 kda omp antigen salmonella typhi for detection of anti-typhoid antibodies in human sera - Hoe, Lau Wai (2004)
In most tropical parts of the world particularly the developing countries, such as Malaysia, Thailand and Indonesia, typhoid fever has remained a major public health problem. The currently available labomtory methods for diagnosis of typhoid fever in endemic areas it.tcluding blood culture, Widal test or other serodiagnostic methods are still unsatisfactory. This is because they failed to meet the ideal criteria of rapidity, simplicity, sensitivity, specificity, cost-effectiveness and practicality. It is well recognized that the indirect enzyme-linked immunosorbent assay (ELISA) has high reproducibility and sensitivity as compared to the currently used methods. In this study, the ELISA was developed and optimized for the detection of serum specific IgG and IgM antibodies to against a 50 kDa Outer Membrane Protein (OMP) antigen preparation of Salmonella typhi. The optimal antigen coating concentration for the 50 kDa OMP was l 0 J.lg/ml for both lgG and IgM ELISA. The ideal dilution of test serum for both IgG and IgM detection was 1 :200 dilution, whilst the horseradish peroxidase-conjugated rabbit anti-human IgG and IgM reagent were each 1:1000 dilution. Both the test antibody and horseradish peroxidase-conjugate reagent were each incubated at 3rc for 1 hour. Enzyme-substrate reaction was 1, 2-0rtho-phenylenediamine dihydrochloride (OPD) in 30% (W N) hydrogen peroxide (HzOz) was used as the enzyme-substrate and the reaction was carried out at room temperature for 5 minutes before the opti~ density (OD) reading was taken. This study evaluated three groups of sera: typhoid fever sera with positive blood culture for Salmonella typhi, non-typhoid sera patients with negative blood culture for Salmonella typhi, and lastly healthy blood donors. Blood Culture method was used as a gold standard for diagnosis of typhoid fever. Antibody concentration in test sera was expressed as Arbitrary Antibody Units (AAU) using a reference standard serum which was assigned 100 Arbitrary units. Quantitation of antibody concentration was carried by superimposing OD readings on the standard curve with dilutions of the reference serum between 1:200 and 20,000 to represented 100 and 1 AAU. For the IgG ELISA, it was found that the coefficient of variation (CV) for both intra-assay and inter-assay was 19.0% and 45.0% respectively. The cut--off value was 47 AAU. The sensitivity and specificity of the ELISA were 42.9% and 100%, respectively, whereas, the Positive Predictive Value (PPV) and Negative Predictive Value {NPV) were 100% and 76.2%, respectively. In contrast, the IgM ELISA had an intra-assay and inter-assay Coefficient of variation (CV) of 20.0% and 27.4%, respectively. The cut-off value for antibody arbitrary unit was 40 AAU. The sensitivity and specificity were 71.4% and 87.5% respectively, whereas, the Positive Predictive Value (PPV) and Negative Predictive Value {NPV) were 62.5% and 89.4%, respectively. These results indicate that both the IgG and IgM ELISA test were not successfully optimized. Amongst the reasons for failure to optimize the assay include a lack of a high titer positive control serum for investigation, and pipetting error in the test.